Factors Affecting The Technical Efficiency Of Inshore Fisheries In Kuala Terengganu, Malaysia - Mohd Suhaimi, Nurul Aisyah (2009)

(untitled)
Marine fish landings in Terengganu have shown a declining pattern starting from year 1985 to 2007. Most of the total landings in Terengganu had come from inshore fisheries. The objective of this study is to determine the factors affecting the technical efficiency of the inshore fisheries in Kuala Terengganu. Data for the study was collected from a survey conducted between June and August 2007 where 100 fishermen in 14 villages were chosen by stratified sampling. Data envelopment analysis (DEA) and Tobit analysis were employed to determine the technical efficiency level and factors influencing among the fishermen. Results of the study show that, most fishing units exhibit a low degree of technical efficiency. This implies that either fishing inputs were used inefficient or insufficient inputs were used in fishery activities. The mean technical efficiency for the sample was estimated to be 55% for the peak season and 40% for the non peak season. About 37% and 62% of the fishermen had less than 40% level of technical efficiency in peak season and non peak season respectively. Management variables (planning, staffing and controlling) and demographic variables (size of horsepower, size of family and formal education) exert positive effect on technical efficiency on inshore fisheries in Kuala Terengganu. These findings suggest that there is much room for improvement in efficiency among a large segment of the inshore fishermen. With appropriate training and using more advanced technologies, fishermen’ level of technical efficiency can be raised.